2015
DOI: 10.1590/1809-4392201401832
|View full text |Cite
|
Sign up to set email alerts
|

Use of anatomical root markers for species identification in Catasetum (Orchidaceae) at the Portal da Amazônia region, MT, Brazil

Abstract: Orchidaceae is one of the largest botanical families, with approximately 780 genera. Among the genera of this family, Catasetum currently comprises 166 species. The aim of this study was to characterize the root anatomy of eight Catasetum species, verifying adaptations related to epiphytic habit and looking for features that could contribute to the vegetative identification of such species. The species studied were collected at the Portal da Amazônia region, Mato Grosso state, Brazil. The roots were fixed in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
0
4
0
8
Order By: Relevance
“…Other orchids (both epiphytic and terrestrial orchids) also showed velamen thickening, while some others did not exhibit velamen cell wall thickening. The epiphytic orchids: Catasetum fimbriatum, C. matogrossense, C. schmidtianum, C. apolloi, C. juruense, C. longifolium, C. osculatum, and C. saccatum had velamen cell wall thickening (da Silva et al 2015). Thickened velamen was also reported in other epiphytic orchids; such as Encyclia patens, Sophronitis pumila, Polystachia estrellensis (Moreira and Isaiaas 2008), Epidendrum secundum (Moreira et al 2013).…”
Section: Velamenmentioning
confidence: 90%
See 1 more Smart Citation
“…Other orchids (both epiphytic and terrestrial orchids) also showed velamen thickening, while some others did not exhibit velamen cell wall thickening. The epiphytic orchids: Catasetum fimbriatum, C. matogrossense, C. schmidtianum, C. apolloi, C. juruense, C. longifolium, C. osculatum, and C. saccatum had velamen cell wall thickening (da Silva et al 2015). Thickened velamen was also reported in other epiphytic orchids; such as Encyclia patens, Sophronitis pumila, Polystachia estrellensis (Moreira and Isaiaas 2008), Epidendrum secundum (Moreira et al 2013).…”
Section: Velamenmentioning
confidence: 90%
“…In the present study, Ascochilus emarginatus had spiral thickening in the cortex, while Taeniophyllum biocellatum, and Thrixspermum subulatum did not exhibit the presence of spiral thickening in their cortex. Other orchid species were reported to have spiral thickening in their root cortical cells, such as Eulophia epidendraea and Malaxis acuminata (Uma et al 2015), Catasetum schmidtianum, and C. juruense (da Silva et al 2015). Leroux et al (2010) suggested that spiral thickening in cortical cells functions as mechanical protection, prevention from desiccation because of root transpiration, and for more efficient water and nutrient uptake.…”
Section: Cortexmentioning
confidence: 99%
“…No Brasil, poucos são os trabalhos realizados com anatomia de Catasetinae, podendo ser mencionados os de Stern e Judd (2001) [20] com a anatomia dos órgãos vegetativos de Catasetinae da região amazônica, o de Pedroso-de-Moraes et al (2012) [21] que descreveu a estrutura radicular de doze espécies nativas brasileiras e o de Silva et al (2015) [22] com o uso de marcadores anatômicos radiculares de oito espécies de Catasetum da Região do Portal da Amazônia, no estado do Mato Grosso. Entretanto, ainda são escassas as informações sobre a organização foliar e radicular de diversas espécies de Catasetum.…”
Section: Introductionunclassified
“…Para orquídeas, as primeiras revisões de anatomia de cunho puramente descritivo (Solereder & Meyer 1930) deram lugar à especulações do ponto de vista funcional dos caracteres anatômicos voltadas a reconhecer os aspectos adaptativos de seus representantes (Dressler 1981;Braga 1987;Silva et al 2006;. Mas, para raízes de Orchidaceae, são necessárias mais informações que possam contribuir com dados concretos da relação entre caractetísticas anatômicas e a taxa de absorção de recursos, havendo poucos trabalhos com essa finalidade atualmente (Herrera et al 2010;Moreaes et al 2012;Silva et al 2015 ). Tendo em vista a carência de dados de cunho morfofisiológico para representantes de Orchidaceae, este estudo teve por objetivos (1) traçar uma correlação entre a caracterização anatômica das raízes de 18 taxa de orquídeas e a taxa de absorção de nutrientes; e (2) avaliar a estrutura da parede celular nas raízes de orquídeas, buscando compreender os mecanismos de absorção e transporte de água.…”
Section: Introdução Geralunclassified